Effect of extrusion-cooking in total carotenoids content in cream and orange flesh sweet potato cultivars - Fonseca,Marcos José de O (2008)
Sweet potato (Ipomoea batatas) is a food crop that supplies energy, minerals and vitamins C and B. Some cultivars are very rich in carotenoids (pro-vitamin A). In this study were evaluated and compared the total carotenoids content of two cultivars and the losses on the dehydrated extruded sweet potato flour. Samples from organic and conventional crops were analyzed, in the form of fresh and dehydrated extruded samples. Total carotenoids content of the fresh product, expressed on wet basis, was of 437 µg 100 g-1 for the cream cultivar and 10,12 µg 100 g-1 for the orange cultivar. After dehydration, losses of total carotenoids were of 41% and 38%, respectively. The fresh orange cultivar presented high total carotenoids content in comparison to the cream cultivar. The extruded orange sweet potato flour showed the lowest losses in total carotenoids. Therefore, the processed flour of orange sweet potato could be used to obtain pre-gelatinized extruded flour with high total carotenoids content.